Incentivizing high impact agricultural innovation for food safety - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2018)
The AgResults Aflasafe pilot implements a pull mechanism to encourage the adoption of Aflasafe technology by agricultural enterprises towards the management of aflatoxin contamination in maize production. In the last four years, the AgResults Pilot model in Nigeria has showed that the private sector can successfully partner with smallholder farmers in adopting innovations such as Aflasafe to improve the quality of crops; it has also shown that this model can support smallholder farmers to grow out of subsistence to market-driven agriculture. Learn and see our experiences and our journey so far in this video.